Effect of Inclusion of Different Levels of Culled Potatoes in Replacement of Maize Grain in the Concentrate Mixture on Feed Intake, Nutrient Utilization and Growth in Sahiwal Calves - Sharma, Ph. Suraj; Datt, Chander .; Baban, Bhong Nana; Kundu, S. S.; Tyagi, Nitin .; Sharma, Vijay Kumar (Indian Journal of Animal Nutrition, 2018)
A study was conducted to find out effect of inclusion of different levels of culled potatoes in place of maize in the concentrate mixture on feed intake and nutrient utilization and growth in Sahiwal male calves. Twenty Sahiwal male calves were divided into four groups of 5 animals each based on their body weight and age and fed as per requirements (NRC, 2001) for 60 days. Maize grain was replaced by culled potatoes @ 0, 25, 50 and 75% on DM basis in groups T1, T2, T3 and T4, respectively. DM intake, digestibility of nutrients (DM, CP, OM, EE, NDF and ADF), nitrogen retention and average daily gains were similar in all the 4 groups. Therefore, maize grain could be replaced by culled potatoes up to 75% in the concentrate mixture having 33% maize without affecting feed intake, growth and nutrient utilization in Sahiwal male calves.